2013
DOI: 10.1177/2325957412473780
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Factors Associated with Initial and Recurrent Methicillin-Resistant Staphylococcus aureus (MRSA) Skin and Soft-Tissue Infections among HIV-Infected Persons

Abstract: HIV control and avoidance of IDU may be useful in reducing rates of MRSA SSTIs among HIV-infected persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 23 publications
0
28
0
4
Order By: Relevance
“…The risk factors indicated as predisposing factors for the susceptibility of people with HIV/AIDS to MRSA are: CD4+T lymphocyte count below 500 cell/mm 3 , HIV viral load of 400 copies/ml or above, use of injectable drugs, old age, prior hospitalization and invasive procedures (7,12) . Based on that, most participants of this study presented most risk factors indicated as predisposing factors for colonization by MRSA in this investigated population.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors indicated as predisposing factors for the susceptibility of people with HIV/AIDS to MRSA are: CD4+T lymphocyte count below 500 cell/mm 3 , HIV viral load of 400 copies/ml or above, use of injectable drugs, old age, prior hospitalization and invasive procedures (7,12) . Based on that, most participants of this study presented most risk factors indicated as predisposing factors for colonization by MRSA in this investigated population.…”
Section: Discussionmentioning
confidence: 99%
“…In further support of a role for T cells in defense against S. aureus SSTI, patients with poorly controlled HIV (as assessed by low CD4+ T cell counts and high viral loads) frequently have recurrent SSTI [36], although there are conflicting data on the importance of CD4+ counts as a predictor of SSTI risk [37]. Patients with atopic dermatitis are also susceptible to S. aureus SSTI, which may be partly due to increased levels of Th2 cytokines and subsequent STAT6 expression, that may increase susceptibility to Hla-induced keratinocyte death [38].…”
Section: Text Of Reviewmentioning
confidence: 99%
“…Vyas et al evaluated initial and recurrent infections with MRSA retrospectively in a cohort of mainly HIV-infected men, with 80 % on ART [17]. Eight percent developed a primary infection; associated risk factors included a CD4 count <500 cells/ml, HIV RNA levels >400 copies/ml, and injection drug use.…”
Section: Bacterial Infectionsmentioning
confidence: 99%